ANDICAM I- and J-band monitoring of bright inner Galactic late-type stars. (19th July 2022) - Messineo, Maria
Abstract: Time-series photometry in the I and J bands of 57 inner Galactic late-type stars, highly probable red supergiant (RSG) stars, is presented here. 38% of the sample presents significant photometric variations. The variations in the I and J bands appear to be correlated, with Δ I ∝ Δ J × 2.2, Δ I variations ranging from 0.04–1.08 mag, and Δ J variations from 0.03–0.52 mag. New short periods (<1000 d) could be estimated for eight stars and range from 167–433 d. This work confirms that the sample is not contaminated by large-amplitude asymptotic giant branch stars. Furthermore, despite the large errors in distance, the period–luminosity diagram suggests that the sample is populating the same sequence as the known Galactic RSGs.